Bumblebee queen mortality and behaviour along roads with varying traffic and road verges with contrasting flowering plant diversity - Dániel-Ferreira, Juliana; Berggren, Åsa; Bommarco, Riccardo; Wissman, Jörgen; Öckinger, Erik (Swedish University of Agricultural Sciences, 2022)
This study makes part of the research project GINFRA – green rights-of-way infrastructure for biodiversity and ecosystem services. The aim of the project was to quantify whether linear infrastructure habitats (road verges and power-line corridors) support biodiversity by assessing the influence of the area of these habitats in the landscape, their contribution to landscape connectivity and population persistence.
The linked data was collected by surveying bumblebee queens during the spring and late summer in 20 sites in Uppland, Sweden. The sites were paired such that half of them had a high flowering plant diversity in the road verge and a gradient in traffic intensity from ~100 to ~6000 vehicles per day, and the other half had a similar gradient in traffic intensity but low flowering plant diversity in the road verge (i.e. regular grass dominated road verges). The surveyor walked a 2 km transect (1 km in each side of the road) and recorded all dead and alive bumblebee queens. The data set consists of 403 observations. Each observation corresponds to an observed bumblebee queen, whether they were found dead or alive and what behaviour they presented when observed. The data was gathered in 4 visits, 2 in spring and 2 in the late summer. Weather information is also present in the dataset, as well as information regarding the average width of the road verge.

The data file Queen_mortality_and_behaviour.csv contains 403 rows and 12 columns. See the general description and the documentation file for more information.

Denna studie är en del av projektet GINFRA – green rights-of-way infrastructure for biodiversity and ecosystem services. Projektets huvudsyfte var att kvantifiera om linjära infrastrukturmiljöer (vägkanter och kraftledningsgator) bidrar till mångfalden av växter och insekter i olika rumsliga skalor. Detta gjordes genom att uppskatta hur linjära infrastrukturmiljöers mängd i landskapet bidrar till mångfalden samt hur mycket de bidrar till landskapets konnektivitet.
Datan samlades in genom inventeringen av humledrottningar på 20 lokaler i Uppland, Sverige under våren och sensommaren 2020. Lokalerna parades så att hälften av dem var artrika vägkanter som hade en gradient i trafikintensitet från ~100 till ~6000 fordon per dag, och den andra hälften hade en liknande gradient i trafikintensitet men hade artfattiga eller gräsdominerande vägkanter. Inventeraren gick en 2 km lång transekt (1 km på varje sida av vägen) och registrerade alla döda och levande humledrottningar. Datauppsättningen består av 403 observationer. Varje observation motsvarar en observerad humledrottning, om de hittades döda eller levande och vilket beteende de uppvisade när de observerades. Datan samlades in vid 4 besök, 2 på våren och 2 på sensommaren. Väderinformation finns också i datasetet, liksom information om vägkantens genomsnittliga bredd.

Datafilen Queen_mortality_and_behaviour.csv innehåller 403 rader och 12 kolumner. Se den allmänna beskrivningen och dokumentationsfilen för mer information.
Mortalitet av humledrottningar längs vägar med varierande trafik och kontrasterande blommande växtdiversitet i vägkanten
Keywords: bumblebees; humlor; Apoidea; Bombus; humlor; Hexapoda; insekter; linear infrastructure habitats; linjära infrastrukturmiljöer; ecological trap; ekologiska fälla; Biological Sciences; Biologi; Ecology; Ekologi